The Experience of Dutch Women Using a Coping Intervention for Oocyte Retrieval: A Qualitative Study - HDL Ockhuijsen; I Ophorst; A Van Den Hoogen (JRI, 2020)
Background: Many women experience oocyte retrieval during an IVF treatment as a stressful and emotionally difficult situation. Women fear the pain as associated with oocyte retrieval. Based on the existing literature, a coping intervention for oocyte retrieval (CIFOR) was developed to deal with the stress and pain during oocyte retrieval. The objective of this study was to explore the experiences of women using coping intervention for oocyte retrieval (CIFOR) while undergoing oocyte retrieval. Methods: For this generic qualitative study, a purposeful sample of fifteen women was gathered from a university clinic in the Netherlands and each participant was interviewed. Background information about the IVF treatment was collected from medical files. Semi-structured interviews were performed approximately 15 min after the OR procedure. Data were analyzed using the Qualitative Analysis Guide of Leuven and processed using MAXQDA. Results: Twenty-five women were approached for this study between January and May 2018. This study identified five themes that were important in the experiences of women using CIFOR: highly valuing the CIFOR, feasible in daily practice, need for information, sense of control and partner’s involvement.  Conclusion: Women highly valued the tool. They found CIFOR feasible in daily practice and it fulfilled their needs for information. In addition, women had a sense of control using the intervention. Future research will involve performing a pilot study according to the Medical Research Council framework with outcomes based on the patient’s sense of control, ability to cope, coping strategies, anxiety and pain.